Kuningas Lear - Shakespeare, William, 1564-1616; Cajander, Paavo Emil, 1846-1913 (Salt Lake City, UT : Project Gutenberg, 2005)
"Kuningas Lear" by William Shakespeare is a tragedy written in late 1605 or early 1606. Set in pre-Roman Britain, the play follows King Lear's catastrophic decision to divide his kingdom among his three daughters based on their declarations of love. When his youngest daughter refuses to flatter him, Lear disowns her, triggering a chain of betrayals, madness, and violence. Known for its dark tone and themes of blindness and madness, the play is regarded as one of Shakespeare's supreme achievements and among literature's greatest works. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_Lear Wikipedia page about this book: https://fi.wikipedia.org/wiki/Kuningas_Lear
Release date is 2005-08-08
Produced by Tapio Riikonen
Keywords: Tragedies (Drama); Fathers and daughters -- Drama; Inheritance and succession -- Drama; Lear, King (Legendary character) -- Drama; Britons -- Drama; Kings and rulers -- Drama; Aging parents -- Drama